Nothing is missing : a memoir of living boldly - Walters, Nicole, 1985- (Simon Element, 2023)
"A profound and gripping memoir by Nicole Walters, the daughter of Ghanaian immigrants who became a self-made multi-millionaire by showing others how to recognize their own strengths-and her own harrowing journey to the discovery that she was worthy all along of the life of her dreams"--